2011
DOI: 10.1111/j.1365-3024.2011.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of serum‐specific IgE in the diagnosis of human cystic echinococcosis

Abstract: Anti-Echinococcus serum immunoglobulin (Ig)E was assessed by the ImmunoCAP system and compared with anti-Echinococcus serum IgG assessed by enzyme-linked immunosorbent assay (ELISA) and Western blot. The ImmunoCAP system revealed very high specificity (one false positive of 110 healthy individuals), low cross-reactivity (one false positive of 58 patients with other diseases) and decreased sensitivity (73.55%). Receiver operating characteristic analysis displayed a beneficial diagnostic value with high accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(43 reference statements)
2
11
0
1
Order By: Relevance
“…Serologic tests, such as enzyme-linked immunosorbent assay, indirect hemagglutination and immunoblot techniques, can be used to confirm the hydatid origin of a cyst diagnosed by imaging techniques. Recently, the quantitative assessment of serum-specific immunoglobulin E by the ImmunoCAP® system has been performed for the diagnosis of hydatid cysts [7]. Elevated serum values of carbohydrate antigen 19.9 were found in the serum of a 69-year-old woman with a palpable mass in her breast, and these levels decreased after resection [8].…”
Section: Discussionmentioning
confidence: 99%
“…Serologic tests, such as enzyme-linked immunosorbent assay, indirect hemagglutination and immunoblot techniques, can be used to confirm the hydatid origin of a cyst diagnosed by imaging techniques. Recently, the quantitative assessment of serum-specific immunoglobulin E by the ImmunoCAP® system has been performed for the diagnosis of hydatid cysts [7]. Elevated serum values of carbohydrate antigen 19.9 were found in the serum of a 69-year-old woman with a palpable mass in her breast, and these levels decreased after resection [8].…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference could be found between the sera of MAR+ and MAR– patients for both specific IgG (data not shown). However, as the signal in this test was only barely above the detection limit, further analysis for the detection of specific IgG to Ves v 5 and wasp venom extract in MAR+ and MAR– patients’ sera was performed by ImmunoCAP, a quantitative standardized method routinely used for the determination of specific IgE [27]. Figure 3 shows that again no significant difference in wasp venom extract-specific IgG was detected in MAR+ and MAR– patients (p = 0.3).…”
Section: Resultsmentioning
confidence: 99%
“…Such an assay is not available for anti-CRISP-2 IgG, and a homemade ELISA was used for the determination of these antibodies. ImmunoCAP is a standardized quantitative method routinely used for the determination of specific IgE, which has been shown to have a significantly higher sensitivity than ELISA [27]. Another explanation may be connected to the fact that CRISP-2 is a protein which is mainly expressed in the male testis [20] and, under normal conditions, remains hidden from the immune system by the blood-testis barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Data in the literature for sensitivity and cross-reactivity of serum anti-Echinococcus IgE differ significantly; most studies report high specificity (99-100%) (Marinova et al, 2011;Chamekh et al, 1992;Khabiri et al, 2006;Afferni et al, 1984;Sjolander et al, 1989;Zarzosa et al, 1999) A recent study using a large panel of sera showed that crude or purified antigens from parasite or hydatid cyst fluid generated a reasonable high specificity (Feng et al, 2010). By using 857 sera from confirmed CE patients and 42 sera from AE patients and 697 sera with different infection and medical conditions showed an overall of 93.4% of specificity with relative low sensitivity 57.4-68.4% (Table 1) (Feng et al, 2010).…”
Section: Immunodiagnosis Of Cystic Echinococcosis In Humansmentioning
confidence: 99%
“…A comparison of the ImmunoCAP system for testing serum IgE compared with IgG-ELISA and IgGWestern blotting revealed the former test had a higher specificity and lower cross-reactivity with a sensitivity of 73.6% (Marinova et al, 2011).…”
Section: Other Recombinant Proteins and Approaches For Immunodiagnosismentioning
confidence: 99%